THINKING OUTSIDE THE SQUARE: NUTRITION SUPPORT IN 18 YR OLD WITH CHRONIC RENAL FAILURE, GASTRECTOMY AND COLECTOMY USING A PAEDIATRIC FORMULA. - K Marks; M Wong; G Thomas; S Alexander; A Magoffin (The Korean Society of Nephrology, 2012)
18 yr old female with EBV lymphoproliferative disorder, B cell lymphoma on background of Crohn's disease, sclerosing cholangitis/autoimmune hepatitis overlap underwent total colectomy and gastrectomy due to life-threatening bleeds. During her 132 day PICU stay, she lost 14kg (23% body weight) and developed CRF. Energy requirements were estimated using Schofield Equation, ideal body weight for height, light activity. Several formulae were compared for total energy, goal rate (jejunal feeds without a colon), osmolality, protein allowance and micronutrient requirements for an 18 yr old female. No adult formulae were suitable in this case. Initially, diluted SuplenaTM (1.7kCal/ml) was used, but weight gain was too rapid and protein intake too low (0.7g/kg/d). Nutrini EnergyTM (1.5kCal/ml) met requirements for: energy, protein (∼1g/kg), micronutrients (except K, Mg and P [see table]). Feed rate (90ml/hr) was well-tolerated; stool output remained 200-300ml/day. Feeds were given over 16/24 for flexibility. Skinfold measures (TSF, MAC) were 25th-50th percentile and she reached goal weight in 4 months. Nutrient Intake % RDI Nutrient % RDI Energy kJ/kCal 9030/2160 98-102 Vitamin A eq 125 Protein g 59 98-101 Thiamin 301 Fluid (mL) 2000 100 Riboflavin 314 Na (mmol) 76 282 (AI) Niacin eq 175 K(mmol) 61 91 (AI)* Vitamin B12 162 Ca (mg) 1296 100 Vitamin C 540 Mg (mg) 245 82* I 144 P (mg) 1080 86* Mo 201 Fe (mg) 21.6 144 Se 108 This patient's clinical complexity made meeting nutritional needs very challenging. Serum Mg levels remained normal, and due to CRF, P and K less than RDI is appropriate. A paediatric formula met adult needs in this unique case: low protein, high energy, and adult micronutrient RDIs.